Podnikatelský záměr - Balcarová, Lucie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Diplomová práce na téma podnikatelský záměr se zabývá rozšířením nabízeného sortimentu společnosti ABC Wood, spol. s.r.o. Podrobně analyzuje současný stav společnosti z hlediska interního i externího prostředí, ve kterém společnost působí. Cílem práce je na základě teoretický poznatků a zjištěných skutečností zpracovat podnikatelský záměr, který by měl vést ke zlepšení celkové pozice společnosti na trhu.

Diploma thesis focused on the topic business plan deals with the product diversification of the company ABC Wood, spol. s. r. o. It contains detailed analysis of the present state of company´s internal and external environment in which the company performs. The aim of this thesis is to create a business plan based on the theoretical knowledge and identified facts. This business plan should lead to the improvement of company´s market position.
Business Plan
Keywords: podnikatelský plán; záměr; projekt; nátěrové hmoty; business plan; contemplation; project; painting material